Protection of Children Involved in Online Prostitution Cases in Terms of Law of Children Protection - Meiliana Nurcahyani; Anang Dony Irawan (Indonesia Law Reform Journal, 2022)
Abstract The purpose of this paper was  to analyze the extent to which the law provides for legal protection for children involved in online prostitution  by using the media of chat applications.  The research method used is a normative legal research method with a statutory approach.  The results showed that for child offenders, provisions in Law No. 11/2012 concerning the Juvenile Criminal Justice System apply. Meanwhile, criminal acts that ensnare perpetrators such as pimps and also service users must also be subject to pidana in accordance with Law Number 17 of 2016 which stipulates the threat of punishment more severe than the Criminal Code.  The participation of the community, relevant institutions and also the government must be more active in following up on this case of online prostitution, the government must strictly revoke applications circulating in the virtual world and set penalties for perpetrators involved in this criminal act. Abstrak Tujuan dari penulisan ini menganalisis sejauh mana undang-undang mengatur tentang perlindungan hukum bagi anak yang terlibat dalam prostitusi online dengan mengunakan media aplikasi chatting. Metode penelitian yang digunakan adalah metode penelitian hukum normative dengan pendekatan peraturan perundang-undangan. Hasil penelitian menunjukan bahwa untuk pelaku anak, berlaku ketentuan di UU No. 11/2012 tentang Sistem Peradilan Pidana Anak. Sedangkan tindak pidana yang menjerat pelaku seperti mucikari dan juga pengguna jasa juga harus dikenakan pidana sesuai dengan Undang-Undang Nomor 17 tahun 2016 yang menetapkan ancaman hukuman lebih berat dibanding Kitab Undang-undang Hukum Pidana. Peran serta masyarakat, lembaga-lembaga terkait dan juga pemerintah haruslah lebih aktif dalam menindaklanjuti kasus ini prostitusi online, pemerintah harus tegas mencabut aplikasi yang beredar didunia maya dan menetapkan hukuman bagi para pelaku yang terlibat dalam tindak pidana ini.